Estimation of Maximum Rapprochement of Flexible Collecting Buses with Drops at Short Circuit - E. G. Panamarenka (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
A simplified algorithm for calculating maximum rapprochement of adjoining phases of collecting buses with drops that is based only on available geometrical span dimensions has been developed in the paper. The paper reveals an opportunity for prohibitive rapprochement and whipping of wires of one phase with the wires of adjoining phase branches and recommendations on its elimination are given in the paper.